Estudo de filmes finos para aplicação em dispositivos fotovoltaicos - Vedovatte, Rafael Misael (2018)
This study aims to characterize films of Perovskite and PEDOT: PSS for application in photovoltaic devices. The inspiration came from the need for new technologies to meet growing global energy demand. The performance of a solar cell is associated with the precursor materials of its layers, its morphology and the structure of the device. For the present research, different deposition techniques, parameters and a solvent treatment were used in order to study the homogeneity and the presence of defects in these layers. These factors are directly related to the cell performance. The studied films were characterized by profilometry, optical and scanning electron microscopy, X-ray diffraction, J-V characterization curves, and 4-point resistance. The use of controlled atmosphere during deposition is a determinant factor for the production of films with the lowest presence of voids. This fact was evidenced by the morphological and structural analyzes of the films.